Relationship between overexpression of ras p21 oncoprotein and K-ras codon 12 and 13 mutations in Turkish colorectal cancer patients - Mustafa AKKİRPİK,; Çiğdem Ataizi ÇELİKEL,; Fikret DÜŞÜNCELİ,; Özgür SÖNMEZ,; Bahadır M. GÜLLÜOĞLU,; Aydın SAV,; Ayşe ÖZER, (Turkish Journal of Gastroenterology, 2019)
-